Male student experience in a maternity nursing clinical course in Saudi Arabia - Fadiyah Jadid Alanazi; Safaa Ibrahim Ahmed; Layan Salem Alenezi; Shaden Anad Almadhrash; Sadeem Falah Alanazi; Sama Sultan Alanazi; Fathia Ahmed Mersal (International Journal of Africa Nursing Sciences)
Objective: This study aims to explore the experiences of male nursing students in maternity clinical courses in Saudi Arabia, identifying the challenges they face and their perceptions of the role of male nurses in a traditionally female-dominated field. The study addresses a significant gap in the existing body of knowledge particularly within the context of Saudi Arabia. While there is a growing body of literature on gender dynamics in nursing, few studies specifically focus on the challenges and perceptions of male nursing students in traditionally female fields. Methods: A qualitative phenomenological approach was employed, utilizing focus group discussions with twelve male nursing students from various regions of Saudi Arabia. Open-end questions was used to collect the data. Thematic analysis was conducted to identify key themes related to their experiences in maternity nursing courses. Results: Four main themes emerged from the data: (1) Attraction to Maternity Nursing—participants expressed reluctance to specialize in maternity nursing due to societal perceptions; (2) Perceptions of Male Roles—students felt out of place in maternity settings, influenced by gender stereotypes; (3) Challenges in Providing Care—participants reported discomfort in interacting with female patients and faced barriers in gaining practical experience; (4) Support and Inclusion—there were mixed feelings about the support received from educators and colleagues, highlighting the need for a more inclusive environment. Conclusions: The study underscores the significant impact of cultural and societal norms on male nursing students in maternity care. It highlights the need for targeted support and educational initiatives to foster a more inclusive environment for male nurses and encourage their full participation in maternity nursing roles.